A NEW CONSIDERATION ABOUT THE ALMOPIA-PAIKON BOUNDARY BASED ON THE GEOLOGICAL MAPPING IN THE AREA OF NEROSTOMA-LAKKA (CENTRAL MACEDONIA, GREECE) - Tranos, M. D.; Plougarlis, A. P.; Mountrakis, D. M. (Bulletin of the Geological Society of Greece, 2007)
Geological mapping along the boundary of Almopia and Paikon zone in the ’Nerostoma’ region, NNW of Lakka village defines mafic volcanogenic rocL·, meta-pelites and radiolarites, thick-bedded to massive micritic limestones and flysch meta-sediments that dip mainly towards SW. Middle-Late Cretaceous fossiliferous limestones overlie unconformably the flysch meta-sediments and are characterised only by a primary foliation SO that dips at shallow angles to the NNW-N. Secondary foliations SI (sub-parallel to SO) and S2 are observed in the meta-clastic rocks. A Dl event caused Fl and progressively F2 folds to which S2 is the axial plane schistosity dipping to SW. This event which has not affected the fossiliferous limestones is related to an oblique convergence or inclined transpression during the Late Jurassic-Early Cretaceous. A D2 event dated in Early Tertiary caused an intense NE-thrusting and S-C cataclastic fabric defining top-to-the NE sense-of-shear. At many parts, the unconformity contact between the fossiliferous limestones and the underlying flysch is obliterated by this thrusting event. As a result, the boundary between Almopia and Paikon zones as paleo-geographically defined in this area seems to be meaningless for the Jurassic-Cretaceous times.